(untitled) (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-0640-2021-3-172-181 Postmodernism is a complex and multifaceted trend in the literature of the second half of the twentieth century. In the process of studying it, students of philology encounter difficulties both in understanding the theoretical base and in applying theoretical knowledge in the analysis of a literary text. The material of the article suggests the stages of work on the study of literary postmodernism, indicates the principles of selection of theoretical concepts, clearly demonstrates information that is significant for understanding the essence of the phenomenon in diagrams. Numerous scientific works present different points of view on the time of the emergence of postmodernism, the nature of its relationship with the previous literary tradition, immerse the consciousness of students in the world of extensive terminology, in which it is difficult for students to see the components necessary for analyzing a postmodern work. By virtue of this, it becomes important to highlight the features characteristic of postmodernism that can represent the uniqueness of the phenomenon under study, establish its place in the system of development of foreign literature, and determine the elements of postmodern aesthetics. The research is associated with the task of deepening students’ skills in analyzing and interpreting a literary text based on a hermeneutic approach. As a result of the work carried out in the course of the practical lesson, the skills of the systemic and holistic perception of the literary process, acquired by the students during the study of the course “History of Foreign Literature”, are consolidated. Key words: postmodernity, postmodernism, modernism, artistic features, text, explicit / implicit quotation, effect of the author’s absence.